The big payoff? Educational and occupational attainments of ethnic minorities in Beijing - Hasmath, R (Routledge, 2013)
Ethnic minority development in Beijing has been marred by deep-seated historical experiences of strained ethnic relations. In spite of this situation, this article demonstrates that ethnic minorities in the capital city have achieved greater educational attainments than the dominant, Han group. Yet, when it comes to their occupational outcomes in high-wage, education-intensive (HWEI) sectors, minorities seemingly pay an 'ethnic penalty'. That is, the Han demographic are disproportionately represented in HWEI occupational sectors. Building upon previous evidence, this article discusses this discrepancy and offers suggestions for improvement.